2016
DOI: 10.18805/ijar.11319
|View full text |Cite
|
Sign up to set email alerts
|

Path analysis of body weight in grower and finisher pigs

Abstract: The aim of this study was to set up direct and indirect casual effects between body weight and biometric measurements of breeding gilts at growing and finishing stages of production using path analysis. Body weights of 50 crossbred (Landrace x Large White) female pigs were measured along with four biometric traits (body length, heart girth, flank-to-flank, height-atwithers) on each animal during growing and finishing stages of production. A computed mean of 1150 measurements per biometric trait taken during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…The records of 394 piglets comprising of 218 male and 176 female, maintained at the farm during 2017-2019, were used for heart girth (circumference around barrel behind fore legs), pounch girth (circumference around barrel before hind legs), height at shoulder (ground to point of shoulder), height at back (ground to point of pin bone), height at fore leg (ground to barrel at fore leg), height at hind leg (ground to barrel at hind leg) and body length (point of wither to starting point of tail) (Banik et al, 2012;Machebe et al 2016). Weight (kg) and other body measurement traits (cm) of all the animals were recorded on birth, at 15 d, 30 d and 42 d (weaning).…”
Section: Measurementsmentioning
confidence: 99%
“…The records of 394 piglets comprising of 218 male and 176 female, maintained at the farm during 2017-2019, were used for heart girth (circumference around barrel behind fore legs), pounch girth (circumference around barrel before hind legs), height at shoulder (ground to point of shoulder), height at back (ground to point of pin bone), height at fore leg (ground to barrel at fore leg), height at hind leg (ground to barrel at hind leg) and body length (point of wither to starting point of tail) (Banik et al, 2012;Machebe et al 2016). Weight (kg) and other body measurement traits (cm) of all the animals were recorded on birth, at 15 d, 30 d and 42 d (weaning).…”
Section: Measurementsmentioning
confidence: 99%
“…A Path model, which is the application of structural equation modeling without latent variables, could provide greater flexibility to test the structure coefficients on a theoretical basis. Although different models were used, the application of this technique is limited and reported in Karacabey Merino sheep (4), Yankasa sheep (33), Sahiwal cattle (17) and Landrace × Large White pigs (13).…”
Section: Introductionmentioning
confidence: 99%
“…Machebe and Ezekwe (2010) estimated BW that included growing (8-15 wk of age) to finishing (16-30 wk of age) gilts using simple linear body measurement of HG (R 2 = 0.95), L (R 2 = 0.91), and FF (R 2 = 0.93). For gilts in these stages of production, Machebe et al (2016) found that HG was the major contributor to BW (R 2 = 0.95), whereas L and FF mostly affected BW indirectly via HG. For gilts at the time of first insemination, the present study's equations included FF and BCS with lower R 2 (R 2 = 0.53).…”
Section: Physiological State Amentioning
confidence: 95%